MANAGEMENT OF FACILITIES AT TENAYAN RAYA AGROTOURISM PARK IN PEKANBARU CITY - Frilia, Annisa; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Facilities are one of the needs of tourists which is very necessary when in a tourist attraction so that tourism managers must always improve good facilities so that visitors become more comfortable. Agrotourism is a tourist spot that utilizes natural or agricultural resources. Tenayan Raya Agrotourism Park in Pekanbaru City is one of the educational agrotourism that has existed for a long time in Riau Province. This study aims to identify the existing facilities in the Tenayan Raya Agrotourism Park and to increase the number of visitors. Based on research that has been done in the field, this research uses qualitative methods with a descriptive approach by collecting data using observation, documentation and interviews. The results of this study aim to improve the quality of facilities that are better and more comfortable when visiting the Tenayan Raya Agrotourism Park, Pekanbaru City. Keywords: Management, Facilities, Agrotourism, Tenayan Raya.